Pilot application of an inflammation and physiological dysregulation index based on noninvasive salivary biomarkers - Andrey I. Egorov; William Xue; Jason Kobylanski; Miyu Fuzawa; Shannon M. Griffin; Timothy J. Wade; Michael Nye (BMC Research Notes)
Abstract Background and objective Noninvasive salivary biomarkers can be used to assess the cumulative subclinical health impacts of social and environmental stressors. We evaluated seven salivary biomarkers of neuroendocrine and immune functions and a group index of physiological dysregulation based on these biomarkers in a pilot survey in a socioeconomically disadvantaged population. Results Participants recruited at subsidized public housing projects in Denver, Colorado, completed a sociodemographic, behavioral, and health questionnaire and used passive drool samplers to collect five saliva samples over the course of 1 day. Samples were tested for the neuroendocrine biomarkers alpha-amylase, cortisol, and dehydroepiandrosterone (DHEA) as well as immune system/inflammation biomarkers C-reactive protein (CRP), interleukin (IL)-1β, IL-6 and total immunoglobulin A (IgA). A composite Inflammation and Physiological Dysregulation Index (IPDI) was calculated as a count of potentially unhealthy values of dichotomized biomarkers. In 20 individuals who completed the survey (average age 46 years, 75% females), allergy to house dust was significantly associated with increased IPDI (adjusted for age) and significantly increased odds of potentially unhealthy values of total IgA, IL-1β, and CRP. Age, obesity, diabetes, allergy to pollen, recent loss of employment, and depression, anxiety, and stress scores from the standard DASS-21 questionnaire were positively but not significantly (0.05 < p < 0.2) associated with IPDI. This project demonstrated an application of a composite index based on noninvasive salivary biomarkers to assess subclinical health impacts of chronic social stressors.